دور التخطيط الاستراتيجي للموارد البشرية في تحقيق الولاء التنظيمي: دراسة حالة البنك الوطني الجزائري ببشار - مقدم, عبد الجليل; عدناني, خولة (جامعة الوادي - University of Eloued, 2020)
The study aimed to identify the role of strategic planning for human resources in achieving the organizational loyalty of the employees of the National Bank of Algeria, by clarifying the availability of the strategic vision and philosophy for strategic planning for human resources, and the level of strategic planning practices for human resources, and it also aimed to identify the level of organizational empowerment Organizational justice, ethical climate and organizational leadership in the National Bank of Algeria, through organizational loyalty. In this study, we relied on the descriptive and analytical approach, whereby questionnaires were distributed to customers of the National Bank of Algeria - Bashar Agency -, and the results were extrapolated by the SPSS statistical analysis program to process the data. The study concluded that strategic planning for human resources plays an important role in achieving organizational loyalty for bank employees, as it is considered the main driver of the competencies and capabilities of the human element.
The role of strategic planning for human resources in achieving organizational loyalty: a case study of the National Bank of Algeria in Bashar
مقال
Keywords: التخطيط الاستراتيجي ; الموارد البشرية ; البنك الوطني الجزائري ; الولاء التنظيمي